SMOKING AND THE WORKPLACE NATIONAL INTERAGENCY COUNCIL ON SMOKING & HEALTH BUSINESS SURVEY (Tufts Archival Research Center, 2007)
National Interagency Council on Smoking & Health business survey on smoking in the workplace. Provides background on smoking and health and their economic implications. Discusses methodology. Charts responses to each question. Concludes that US companies have reduced workplace smoking, provide smoking cessation programs, and desire to develop or expand smoking programs for employees.